Heritability and repeatability estimates of first service conception and first cycle calving in Angus cattle - Foxworthy, Heather, author; Enns, R. Mark, advisor; Speidel, Scott E., advisor; Thomas, Milton G., committee member; Callan, Robert, committee member (Colorado State University. Libraries, 2019)
Described as the ability of an individual to conceive and remain pregnant, fertility remains one of the largest economic impacts on cattle producers. Infertility and(or) sub-fertility in the cow herd can result in financial losses due to a reduction in calf crop, lower quality calves, and increased breeding and replacement costs. Improving reproductive efficiency via altered management and selection could prove useful for cattle managers to minimize these costs while increasing genetic gain and income. However, historically the investigation of fertility traits has been minimal due to the binary nature of many of the traits making analysis difficult. In addition, given the nature of the phenotypes, heritability estimates of fertility traits are generally low, suggesting minimal genetic influence and therefore slow rates of genetic gain. First service conception (FSC) is a binary trait that describes the outcome of the first service of artificial insemination (AI) with success or failure phenotypes. Furthermore, a trait termed first cycle calving (FCC) describes the ability of a female to calve within a 21-day period of the due date based on the initial opportunity for conception in the first 21 days of the breeding season. The objectives of this thesis included the further investigation of the influential factors, genetic and environmental, on the success of first service conception and first cycle calving with the end result estimates of heritability and repeatability for these traits in Angus cattle. Data used for this analysis was sourced from the Colorado State University Beef Improvement Center (1985 to 2018; CSU-BIC; N = 8,206) near Saratoga, Wyoming where an Angus cow herd is managed for research purposes. The data used included breeding and ultrasound records, as well as data on the resulting and previous calves. Model selection resulted in fixed effects of birth year (P < 0.001), mating type (insemination based on estrus or during mass mating; P < 0.001), contemporary group consisting of synchronization protocol, semen type, and mating year (P < 0.001), previous calving ease (P < 0.001), and covariates of mating age in days (P < 0.01), and post-partum interval (P < 0.001) for both FSC and FCC. Variance components for the two traits were estimated using a REML procedure and then combined into estimates of heritability and repeatability. Analysis resulted in estimates of 0.03 ± 0.02 and 0.15 ± 0.03 for FSC and FCC, respectively for both heritability and repeatability when considering the entire female reproductive lifespan. When observations were segregated into immature and mature categories of beef females one to four years of age at mating and five years or greater, differences in parameter estimates became apparent. Estimates of heritability for FSC in immature and mature females were 0.04 ± 0.04 and 0.02 ± 0.05, respectively while repeatability was estimated for the two categories at 0.04 ± 0.04 and 0.08 ± 0.04. These estimates for mature females suggested a detectable influence of the permanent environment; however, all estimates are considered low for their respective parameter. When estimating the parameters for FCC, heritability was estimated at 0.04 ± 0.07 and 0.21 ± 0.04 for immature and mature female categories, respectively; while repeatability values were 0.11 ± 0.07 and 0.21 ± 0.04, respectively. These estimates suggest a permanent environmental effect; however, estimates of both parameters for immature females were low, while those for mature females can be classified as moderate. The findings suggested that altering temporary environmental management should remain the most critical factor when improving female reproduction. The largest genetic contribution was for FCC in mature females resulting in more potential for selection and culling based on the phenotype for that trait.
Keywords: first cycle calving; repeatability; beef cattle; reproduction; first service conception